Toxicity effect of Centella asiatica Linn. extract on mice (Mus musculus) organ and tissue - ., Praptiwi; Wulansari, Dewi; ., Chairul (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Toxicity test ofCentella asiaticaLinn. water extract had been carried out. Extract were administered via oral, single and daily doses in mice (Mus musculus). The effect of extract on organs and tissue were evaluated by observing the pathology anatomy of heart, liver and kidney and alsoLD50 value. The influences of acute and sub-chronic toxicity on morpho-anatomy organs and histo-pathology tissue were in accordance with LD50experiment. The results of morpho-anatomy showed that all organs were still in normal condition at low dose treatment, but stain and white spots appeared on liver, black spot on heart and white spots on kidney at higher dose. Histo-pathology indicated that low dose administration of extract resulted that, all of tissue observed were in good and normal condition, but at higher dose resulted injure of muscle fibres and also injure of nucleus cells of heart tissue also the colour of liver tissue was brick red and white stain manifestation (because the damaged of cells and accumulation of leucocytes). Degeneration and congestive sinus occurred in liver tissue, while necrosis and protein degeneration formed in kidney because of glomerulus membrane damaged. LD50 of Centella extract was 13.6 g/kg. This dose indicated that Centella extract is slightly toxic (5 - 15 g/kg), so that it is suggested that if it was used in phyto-therapy had to be under supervision of an expert or specialist and administered in low dose and short period.Keywords : Centella asiatica Linn; extract; acute and subchronic toxicity; anatomy pathology